Key Aspects of Humanising Organizations - Elena V. LYLOVA; Irina O. SADOVNICHAYA (Communications of International Proceedings, 2021)
The article describes the main approaches to the disclosure of the humanization concept in the context of management and organization theory. The fact is that the human-oriented approach in business is a part of such significant global trends as the knowledge economy development, corporate social responsibility, and socially oriented management. In the core of the person-oriented concept of business is a person (employee, customer, society as a whole). The philosophy of such an organization is based on both humanistic values in regard to its own employees (professional development of staff, care for the health of employees, etc.), and the extent to which the business is honest with everyone at all its levels, including nature.
Keywords: Human-Centered Design; Humanising Organizations; Corporate Social Responsibility; Holacracy.